HMGB1-antagonism exerted by glycyrrhizin could be fruitful against COVID-19. - Ciprandi, Giorgio; Bellussi, Luisa Maria; Damiani, Valerio; Passali, Desiderio (Acta Biomedica Atenei Parmensis, 2021)
The COVID-19 pandemic era is causing a relevant issue for the health. There is no specific drug able to antagonize the SARS-CoV-2 infection. As a consequence, there is growing interest about potential molecules able to contrast infection. In this regard, HMGB, an alarmin, may play a relevant role in pathogenic mechanisms induced by SARS-CoV-2. As HMGB1 is antagonized by glycyrrhizin, this substance could be potentially useful as ancillary treatment in COVID-19.